Analýza vybraného podnikatelského subjektu pomocí vybraných metod - Mačto, Daniel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce je zaměřena na analýzu vybraného podnikatelského subjektu. Na základě zkoumaných analytických metod vnějšího a vnitřního prostředí podniku je zhodnocena celková situace podniku. V závěru práce jsou uvedeny návrhy a doporučení na zlepšení stávající situace.

The diploma thesis focuses on the analysis of the selected business subject. Based on the analyses using analytical methods of the external and internal environment of the company, the overall situation of the company has been evaluated. At the end of the paper there are presented suggestions and recommendations for improving the current situation.
Analysis of the Selected Company by Using the Selective Methods
Keywords: Business analysis; PESTLE analysis; Porter's model of Five Forces; Kralicek Quick test; Marketing mix; SWOT analysis.; Analýza podniku; PESTLE analýza; Porterův model pěti sil; Kralicek Quick test; Marketingový mix; SWOT analýza.